Relationship Quality in the Context of Computer-Mediated Communication - A social constructionist approach - Jens O. Meissner (University of Basel, Center of Business and Economics (WWZ), 2005)
This paper contributes to possible answers to the question: What are the effects of computermediated communication on relationship qualities in organizations? To answer this question without oversimplifying the phenomena an adequate research methodology has to be found. First, the interrelationship between computer-mediated communication (CMC) and relationship quality is reviewed. CMC-theory will be described from three main perspectives and the risks and chances for relationship quality will be shown. The review indicates that most studies in the field are founded on a positivistic basis. Relationships are treated as static dyads neglecting contextual factors. Thus, the insight into relational processes in computerized environments remains limited. As an alternative a research methodology based on the epistemological stance of social constructionism is proposed. It will be explained, how the researchers' view can be broadened by applying the method of the `narrative interview' in practice based studies in computer-mediated contexts. In the concluding part, the contribution of this approach to research and practice will be discussed.
Keywords: 330; Computer-mediated communication; relationship quality; social constructionism